Abatement of neurobehavioral and neurochemical dysfunctions in cerebral ischemia/reperfusion injury by Tetrapleura tetraptera fruit extract. (10th January 2021) - Saliu, Ibrahim Olabayode; Amoo, Zainab Abiola; Khan, Mohammad Faheem; Olaleye, M. Tolulope; Rema, Velayudhan; Akinmoladun, Afolabi C.
Abstract: Ethnopharmacological relevance: Tetrapleura tetraptera Taub. (family Fabaceae), is generally found in the lowland forest of tropical Africa. Its leaves and fruits are traditionally used in West Africa for the management of brain disorders. Aim of the study: This study evaluated the effect of Tetrapleura tetraptera methanol fruit extract (TT) on bilateral common carotid artery occlusion-induced cerebral ischemia/reperfusion (I/R) injury in male Wistar rats. Materials and methods: Rats pretreated with TT for 7 days before a 30 min bilateral common carotid artery occlusion and reperfusion for 24 h were assessed for neurobehavioural deficits. Cortical, striatal and hippocampal oxidative stress, pro-inflammatory events, electrolyte imbalance and neurochemical dysfunctions, as well as hippocampal histopathological alterations, were also evaluated. HPLC-DAD analysis was performed to identify likely compounds contributing to the bioactivity of the extract. Results: TT reduced I/R-induced behavioral deficits and ameliorated I/R-induced oxidative stress by restoring reduced glutathione level, increasing catalase and superoxide dismutase activities, and also reducing both lipid peroxidation and xanthine oxidase activity in the brain. TT attenuated I/R-increased myeloperoxidase and lactate dehydrogenase activities as well as disturbances in Na + and K + levels. Alterations elicited by I/R in the activities of Na + /K + ATPase, complex I, glutamine synthetase, acetylcholinesterase, and dopamine metabolism were abated by TT pretreatment. TT prevented I/R-induced histological changes in the hippocampus. HPLC-DAD analysis revealed the presence of aridanin, a marker compound for Tetrapleura tetraptera, and other phytochemicals. Conclusions: These findings indicate that Tetrapleura tetraptera fruit has a protective potential against stroke through modulation of redox and electrolyte imbalances, and attenuation of neurotransmitter dysregulation and other neurochemical dysfunctions. Tetrapleura tetraptera fruit could be a promising source for the discovery of bioactives for stroke therapy. Graphical abstract: Image 1 Highlights: Tetraptera tetrapleura fruit extract improved neurobehavioral deficits in ischemia/reperfusion-induced brain injury. Cerebral redox stress in the injured rats was ameliorated by pretreatment with extract. The extract mitigated brain inflammation, mitochondrial dysfunction and acidosis in injured rats. Neurotransmitter dysregulation was modulated by the extract in brain hippocampus, striatum and cortex of rats. Aridanin and other bioactive compounds were identified in the extract of Tetraptera tetrapleura fruit.